Irrigation development and agricultural water management in Rwanda: a systematic review - Mabhaudhi, T.; Dirwai, Tinashe Lindel; Taguta, C.; Kanda, E. K.; Nhamo, L.; Cofie, Olufunke O. (Springer, 2025)
Most African countries rely on food imports and cannot feed their populations. The most vulnerable region to chronic food insecurity is sub-Saharan Africa (SSA) where agriculture is mainly rainfed and therefore threatened by climate change and variability. Irrigation is one of the main solutions for stabilizing yields and reinforcing food security, yet it is underdeveloped in most parts of Africa. However, irrigation consumes the largest amount of water than the other sectors; thus, exploring and implementing ways of producing more yield per unit volume of water is necessary. To counter food insecurity and improve agricultural water management, the African Union (AU) developed a framework for irrigation development and agricultural water management (IDAWM) to be adopted in all the member states in the continent. This framework is premised on four development pathways, namely, improved water control and watershed management in rainfed farming, farmer-led irrigation development (FLID), irrigation scheme development and modernization and the use of unconventional water for irrigation. Therefore, this review sought to assess the status, challenges, and opportunities of IDAWM in Rwanda. The systematic review adopted the PRISMA-P (Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols). The results indicated that Rwanda has adopted various strategies such as terraces, contour bunds, and water harvesting to address soil erosion and improve water storage. Irrigation is practised in three ways: marshland, hillside, and small-scale irrigation technologies, which are faced with several challenges, such as land use policy and inadequate participation, which hinder progress in FLID. Inadequate private sector involvement hinders investment in the modernization of irrigation schemes in Rwanda. Inadequate sewerage and wastewater treatment infrastructure limits wastewater reuse in irrigation. The bright spots are anchored in sound and progressive agricultural policy, abundant water resources, favourable climatic and ecological conditions and a ready regional market.